Why Has China’s Fertility Rate Plummeted in the Past Decade? An Investigation of Fertility Intentions and Influencing Factors Among Single, Unmarried Women of Childbearing Age in China - Yantong Zhou; Ying Bian (Social Sciences)
Background/Objectives: Currently, the type of population reproduction in China has changed to “low birth, low death, low growth”. Additionally, as the number of single people has increased and the number of women of childbearing age has decreased, the growth of the total population was bound to show a negative trend. Therefore, this study aimed to understand what factors influence fertility intentions from the perspective of single, unmarried women. Methods: We designed our own online questionnaire and collected information on fertility intentions from single, unmarried women of childbearing age (18–49 years). A total of 741 questionnaires were collected, with a valid response rate of 92.6%, and the Theory of Planned Behavior model was integrated into the questionnaire survey. Statistical analysis was performed via SPSS 24.0, and AMOS 24.0 software’s analysis of variance was used to determine whether there were differences in attitudes towards fertility intentions among respondents. Structural equation models were constructed via AMOS software for validation factor analysis and path analysis. Results: There was a significant difference (p < 0.05) in “monthly income”, “net family income”, “health status”, and “only-child status”. Structural equation modelling revealed that fertility attitudes (β1 = 0.301, p < 0.05), subjective norms (β2 = 0.295, p < 0.05), and perceived behavioural control (β3 = 0.146, p < 0.05) positively influence fertility intentions. Conclusions: The fertility intentions of single, unmarried women of childbearing age in China are influenced by many factors. Therefore, society should pay more attention to the rights and interests of single, unmarried women and provide a better social environment for childbearing; in addition, it is possible to appropriately relax the fertility policy of single births to improve the low fertility rate in China.